Powrót do świata Dzieje uwagi w filozofii i literaturze XX wieku - Król, Zofia (Nowa Humanistyka, 2013)
The author identifies selected aspects of the history of attention and exposes the peculiar relation between philosophy and literature against this background. The task of describing the world, not finished by phenomenology, is taken up by attentive poetry: it can complete the project of portraying the visible world, while keeping the rules of perceptive faith, but also being mindful of the constraints of language at the same time. After breaking contact between word and object, the poet becomes the one who brings the spirit of mankind closer to the world. In the context of twentieth-century dilemmas and projections, attention turns out to be not only a simple consequence of a certain aesthetic choice, but instead, choosing attention gains a crucial importance, rendering it a tool of re-vindicating the lost reality. Attentive poetry, that is such poetry, which does not allow itself to get carried away with language in whichever direction, but tames its anarchy, and does not accept a finished world, rejecting the temptation of relying on easy knowledge, is complemented by attentive reflection in this study: a reflection which is not prone to putting too much faith in the exclusivity of its own accomplishments. (excerpt from a review by Prof. Piotr Śliwiński)